GOODS DELIVERY SYSTEM BY USING THE SHIP IN PT. NURKARYA SEJAHTERA - Yenny Yenny; Irfan Irfan, Skom, MM (Jurnal Sistem Informasi, 2001)
The use of computers in our lives has been very widespread and popular in thecommunity. Not only limited in the work environment, but also in everyday life. Incorporate environments, computers are tools that are absolutely necessary in order toachieve competitive advantage, especially before the era of free markets. On a freightforwarder company needed a computer application programs such as program inputgoods, the customer input program, the program deletes items, the program deletesthe customer, program editing articles, edit the program customer, the transactionprogram, the program reports and receipts and all these programs the program mayuse the program dBase application. By using a computer application program, thecompany will gain in terms of ease of filing, preparing reports, creation of supportingdocumentation and the ease in running the business. The development of computerhardware technology, supported by the rapid development of hardware techniquesenable the emergence of applications that are not possible before and the making ofthe application programs become easier and faster